PENGARUH DOSIS PUPUK VERMIKOMPOS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium Ascalonicum L.) VARIETAS BIMA - Afansya, Irre; Mahmud , Yudhi; Dwimartina, Fina (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2025)
Shallots are a horticultural crop that is used as a spice for cooking every day. The community's demand for shallots continues to increase, but the production level is still low. Efforts that can be made to increase the production of shallot plants are by using vermicompost fertilizer. Vermicompost fertilizer is a fertilizer from composting organic waste whose fermentation process is assisted by earthworms, so it is useful for increasing onion production. This study aims to determine the effect of vermicompost fertilizer dosage on the growth and yield of the best shallot plants. The research was carried out in the rice fields of Pekandangan Village, Indramayu Regency, in March – May 2024. The experimental design used in this study was a Group Random Design (RAK) consisting of 5 treatments that were repeated 5 times each. The 5 treatments of vermicompost fertilizer doses are V0 = control, V1 = 10 tons/ha, V2 = 20 tons/ha, V3 = 30 tons/ha, and V4 = 40 tons/ha. The results showed that there was an effect of the use of vermicompost fertilizer on all components of the growth and yield of shallot plants at the best dose of 30 tons/ha, with a yield of 0.33 tons/ha. Keywords: Vermicompost Fertilizer, Growth and Yield, Shallot Plants, Bima Varieties, Horticulture.